PENGARUH FINANCIAL DISTRESS DAN INTENSITAS ASET TETAP TERHADAP PENGHINDARAN PAJAK PERUSAHAAN DENGAN LEVERAGE SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA DALAM PERIODE 2017-2021 - Husada, Era Vivianti (Publika Citra Media, 2024)
The aim of this research is to test and analyze the effect of financial distress, fixed asset intensity on tax avoidance with leverage as moderation. The sample for this research uses logistics and transportation companies listed on the Indonesian stock exchange for the 2017-2021 period. The data analysis method uses multiple regression analysis using SPSS version 25 software by carrying out several testing stages. The results of the research show that financial distress has a significant effect on tax avoidance, while fixed asset intensity has no effect on tax avoidance, while Leverage Moderation on the Relationship between Financial Distress and Tax Avoidance and Leverage Moderation on the Relationship between Fixed Asset Intensity and Tax Avoidance have a significant influence. Simultaneously, the variables financial distress and fixed asset intensity simultaneously or jointly influence tax avoidance with leverage as moderation.